2006
DOI: 10.1111/j.1460-9568.2006.04867.x
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone reverses the spatial memory enhancements initiated by tonic and cyclic oestrogen therapy in middle‐aged ovariectomized female rats

Abstract: While some research has indicated that ovarian hormone therapy (HT) benefits memory and decreases risk of Alzheimer's disease in menopausal women, several newer studies have shown null or detrimental effects. Despite the null and negative cognitive findings, the numerous studies showing positive effects beg the question of what factors determine whether HT acts as a neuroprotectant or a risk factor for brain functioning. Using middle-aged female rats, we directly compared six HTs. We evaluated the effects of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
148
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(169 citation statements)
references
References 92 publications
(163 reference statements)
19
148
1
1
Order By: Relevance
“…For example, we recently reported that, although P4 treatment in female OVX rats did not affect the extent of kainateinduced neuron loss, it completely blocked E2 neuroprotection (Rosario et al, 2006a). Similarly, continuous P4 treatment has been reported to inhibit E2-mediated increases in neurotrophin expression (Bimonte-Nelson et al, 2004) and spatial memory performance (Bimonte-Nelson et al, 2006). One particularly interesting component of this relationship with hypothesized clinical relevance is the effect of continuous versus cyclic P4 treatment.…”
Section: Discussionmentioning
confidence: 97%
“…For example, we recently reported that, although P4 treatment in female OVX rats did not affect the extent of kainateinduced neuron loss, it completely blocked E2 neuroprotection (Rosario et al, 2006a). Similarly, continuous P4 treatment has been reported to inhibit E2-mediated increases in neurotrophin expression (Bimonte-Nelson et al, 2004) and spatial memory performance (Bimonte-Nelson et al, 2006). One particularly interesting component of this relationship with hypothesized clinical relevance is the effect of continuous versus cyclic P4 treatment.…”
Section: Discussionmentioning
confidence: 97%
“…It has been well-established that estrogens influence memory and cognition [7,8], decrease the risk and/or delay the onset of neurological diseases (e.g., AD and PD), and attenuate the extent of cell death that results from a variety of insults involving ROS-induced oxidative stress implicated among others in stroke or neurotrauma [9,10]. Various in vitro and in vivo models show that estrogens are capable to protect neurons in a concentration range of 0.1 nM to 50 µM suggesting the involvement of different modes of action [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining preclinical research has been done on ovariectomized females treated with 17β-estradiol with results showing the beneficial effect of estrogen on cognition (Table 1) [48][49][50]. Metaanalyses of HT effect on cognition revealed that time-limited positive estrogen treatment effect was seen in women who had recently undergone surgical menopause [51].…”
Section: Modelling Of Human Menopausementioning
confidence: 99%
“…However, animal studies more commonly use subcutaneous pellets and silastic capsules to deliver HT (Tables 1 and 2) [49,83,78,88,90].…”
Section: Ht Dose and Route Of Administrationmentioning
confidence: 99%